2021
DOI: 10.1007/s40820-021-00671-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond-Assisted Ultra-Stable and Fast Aqueous NH4+ Storage

Abstract: Aqueous ammonium ion batteries are regarded as eco-friendly and sustainable energy storage systems. And applicable host for NH4+ in aqueous solution is always in the process of development. On the basis of density functional theory calculations, the excellent performance of NH4+ insertion in Prussian blue analogues (PBAs) is proposed, especially for copper hexacyanoferrate (CuHCF). In this work, we prove the outstanding cycling and rate performance of CuHCF via electrochemical analyses, delivering no capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 67 publications
(52 reference statements)
0
74
0
Order By: Relevance
“…However, the excessive use of traditional energy produces carbon dioxide and other pollutants, causing serious ecological problems. To solve these environmental problems, scientists are beginning to explore renewable energy sources to reduce environmental pollution and meet the needs of social development [1][2][3][4][5]. However, these clean energy sources generally have the disadvantages of location dependence [6][7][8][9][10], high cost and low efficiency, which restrict their large-scale applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the excessive use of traditional energy produces carbon dioxide and other pollutants, causing serious ecological problems. To solve these environmental problems, scientists are beginning to explore renewable energy sources to reduce environmental pollution and meet the needs of social development [1][2][3][4][5]. However, these clean energy sources generally have the disadvantages of location dependence [6][7][8][9][10], high cost and low efficiency, which restrict their large-scale applications [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al also found an interesting hydrogen chemistry in CuHCF when NH 4 + inserted. [ 68 ] As discussed above, the excellent reversible performance of NH 4 + intercalation in PBAs has achieved. To excavate the mechanisms, a joint theoretical and experimental study were applied to analyze the results.…”
Section: Aqueous Batteries With Nonmetal Cations As Charge Carriersmentioning
confidence: 96%
“…In their recent work, they studied the performance of NH 4 + intercalation in copper hexacyanoferrate (CuHCF), and there was nearly no capacity fading after 3000 cycles. Moreover, a new NH 4 + diffusion mechanism was proposed, [ 68 ] which was also discussed in the following section. Wang and co‐workers studied NH 4 + intercalation in emeraldine salt polyaniline (ES‐PANI).…”
Section: Aqueous Batteries With Nonmetal Cations As Charge Carriersmentioning
confidence: 99%
“…In Figure and Table 1 , we have summarized the various electrode materials and electrolytes used for aqueous AIBs. [ 78–101 ] Furthermore, we overview and discuss the research status of these systems.…”
Section: Research Overview Of Aqueous Aibmentioning
confidence: 99%
“…[ 82,84 ] Most recently, Shu's team also explored three other new PBAs cathodes, Fe 4 [Fe(CN) 6 ] 3 (Fe‐PBs), (NH 4 ) 1.81 Cu II 0.8 Cu I 0.2 [Fe III 0.2 Fe II 0.8 (CN) 6 ] 0.95 (N‐CuHCF), and Cu 2.95 [Fe(CN) 6 ] 1.69 (Cu‐PBs), for aqueous ammonium‐ions storage. [ 90 92,93 ] For Cu‐PBs electrode, [ 93 ] a reversible capacity of 76 mAh g –1 and discharge plateau of ≈0.75 V (vs Ag/AgCl) with very small polarization can be achieved ( Figure A). Cu‐PBs also exhibited excellent rate capability and long‐term cycling performance: the reversible capacities are 76, 72, and 71 mAh g −1 at different current rates from 1, 35, to 50 C, corresponding capacity retention of as high as 93.4% at 50 C (Figure 5B); and high capacity retentions of 100% after 3000 cycles, 74.5% after 23 000 cycles and 72.5% over 30 000 cycles at 1 C, 30 C, and 50 C respectively.…”
Section: Research Overview Of Aqueous Aibmentioning
confidence: 99%